CUSTOMER LOYALTY ANALYSIS THROUGH CUSTOMER SATISFACTION: THE IMPACT OF DIGITAL MARKETING AND CUSTOMER PERCEIVED VALUE AT BOBOCABIN BANDUNG - Malika Aura Saqina; Faizal Hamzah (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study aims to analyze the influence of digital marketing and customer perceived value on customer loyalty through customer satisfaction at Bobocabin Bandung. The development of nature-based accommodation and glamping has encouraged hospitality providers to strengthen digital marketing strategies and improve customer value in order to maintain competitiveness. This study employed a quantitative approach with an explanatory research design. The population consisted of customers who had stayed at Bobocabin Bandung, including Cikole, Ranca Upas, Sukawana, and Pangalengan. Data were collected through an online questionnaire using purposive sampling, with 150 valid responses analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that digital marketing and customer perceived value have positive effects on customer satisfaction and customer loyalty. Customer satisfaction also has a positive effect on customer loyalty and mediates the relationship between digital marketing, customer perceived value, and loyalty. These results suggest that customer loyalty is formed through the integration of effective digital marketing, strong perceived value, and satisfying accommodation experiences. The study contributes to marketing management literature in the context of technology-based nature accommodation and provides practical implications for Bobocabin management in improving digital engagement, service quality, perceived value, and long-term customer loyalty.